Acquisition Motive, Stock Market Performance, and Slack Resources as Moderating Variable - Wisudanto; Andini Pitaloka; Astri Irmaulidiyah (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Acquisition is a restructuring activity with different risks depending on the motive used by the company. This study aims to identify the relationship between acquisition motives and stock market performance moderated by slack resources in the acquirer companies. This study observed 65 companies in Indonesia listed on the Indonesia Stock Exchange that performed acquisitions in 2010 – 2020. The data were analyzed using the multiple linear regression technique. The data were analyzed using the multiple linear regression technique. The study concluded that the exploratory motive negatively affected stock market performance. Meanwhile, the moderating variable of slack resources was reported to weaken the negative effect of exploratory motive on stock market performance. This research suggests managers should make a careful decision regarding the acquisition motives that will be used by a company. In addition, they must ensure sufficient slack resources during the acquisition as the process may impact the stock market performance. Thus, investors must carefully observe the acquisition motives and possible risks that might harm their investment. Keywords: exploration acquisition, exploitation acquisition, stock market performance, slack resources, signaling theory